Insect pests of groundnut (Arachis hypogaea L.), nature of damage and succession with the crop stages (Bangladesh Journal of Agricultural Research, 2014)
Thirty six species of insect pests were found to infest the different growth stages of groundnut crop at Gazipur, Bangladesh during the rabi seasons of 2008-09 and 2009-010. Among the recorded pest species, the hairy caterpillar, Spilarctia obliqua ( Walker); common cutworm, Spodoptera litura F.; jassid, Empoasca terminalis Distant ; leaf miner, Stomopteryx nerteria M. and leaf roller, Anersia ephippias (Meyr.) were considered as the major pests, while the rests were of minor importance on the basis of their population densities/plant, nature and extent of damage and yield reductions. Most of the major and minor pests infested during the vegetative to pre-maturity stages (45-95 DAS) and the maximum infestation occurred during pod formation and pod filling stages (50- 80 DAS) of the crop in both the years. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20429 Bangladesh J. Agril. Res. 39(2): 273-282, June 2014